Indigenous Territoriality and Re-existence in the Amazon Frontier:: The Rikbaktsa People and the Escondido Indigenous Land, Mato Grosso, Brazil - Almeida, Juliana; Athayde, Simone; Castorino, Adriano; Seluchinesk, Rosane; Albernaz, Rosane (Sustainability in Debate, 2016)
This paper presents the results of the project "We are the others: Identity and Territory Rikbaktsa”, developed under the Lato Sensu Specialization Course "Collaborative Management of Complex Social-ecological Systems in the Brazilian Amazon. The objective of the project conducted by the group of participants who focused on indigenous issues was to assess the social-ecological resilience of the Rikbaktsa indigenous people within the Escondido Indigenous Land (Cotriguaçu, Mato Grosso). The methodology was adapted from a tool developed by the group "Resilience Alliance", which enabled exploratory research focusing on the subjects: territorial reconfiguration from the 1950s; forms of use and occupation of the Escondido indigenous land; as well as challenges and lessons learned for the development of collaborative research methodologies with indigenous populations. Important attributes were identified for the resilience of the "Rikbaktsa System", in addition to factors of risk that threaten the territorial processes and resistance in which the Rikbaktsa are currently engaged. We also present reflections and recommendations for the application of concepts and methods of the complex social-ecological systems approach and principles of collaborative management with Amazonian indigenous peoples.